GERAKAN PEMBARUAN HUKUM LINGKUNGAN INDONESIA DAN PERWUJUDAN TATA KELOLA LINGKUNGAN YANG BAIK DALAM NEGARA DEMOKRASI - Santosa, Mas Achmad; Quina, Margaretha (Jurnal Hukum Lingkungan Indonesia, 2014)
Environmental law reform movement promotes the realization of good environmental governance, rule of law, and democracy. Numerous advocacy results conducted by this movement has been recorded in the legal instruments, national and international regulation and policies, landmark judges decision, until civil society initiatives. This article will identify the important developments and the contribution of civil society, academics, and other related elements as a reference for the further development of good environmental governance